A challenge to change developments in feminist theology and feminist Christology - Bons-Storm, Riet (HTS teologiese studies, 2005)
Contextual theologies have made it clear that context, and the particular experiences a context gives, shapes thinking about the Divine and the world into a particular, contextual theology. Feminist theologians stress the point that the life-experience of women in general – and every woman of flesh and blood in particular – works as a context, seeing the world, thinking about the Divine from a particular perspective. The critique of feminist theologies is aimed in the first place to the presumptions and assumptions underlying texts, customs and politics. Feminist theologians ask basic questions about the acquisition of theological knowledge that exposes the cultural conditioning of Christian belief. This review article on the work of Lisa Isherwood and Dorothea McEwan demonstrates how many feminist theologians find in “Process Thought” a way of thinking that avoids the suppositions these presumptions and assumptions make.